Carbon isotope fingerprinting palaeo fluid inclusion gases using a crushing-trapping technique. Issue 1 (1st December 2018) - Gong, Se; Sestak, Stephen; Armand, Stephane; Vergara, Tania
Abstract : Carbon isotope fingerprinting has been widely used to study gas origin, maturity and gas-source correlations. However, natural gas accumulation in gas reservoirs can be affected by secondary alteration processes. In contrast, palaeo gases trapped in fluid inclusions (FIs) are free of any secondary alterations that may have occurred in the reservoir. FIs are normally less than 10 um in diameter, hence the gases trapped are at trace level amounts. An online crushing-trapping system has been developed in this study which enabled carbon isotope analyses of hydrocarbon gases which are normally in low concentrations. The crushing-trapping system mainly comprises of a gas-tight crusher and a gas concentrator interface module. The micro-trap is a critical part of the gas concentrator as it collects and concentrates all the released FI gases which results in sharp chromatographic peaks. This novel design is very sensitive, making it an increased challenge to obtain an acceptable blank before running samples. A clean blank is very important for such trace-level gas analysis. System blank results show that there are no hydrocarbon gases but trace amounts of CO2 (20 mV) detected in the blank. These trace amounts of CO2 in the blank have no influence on the carbon isotope calculation. It was found that no isotope fractionation was attributable to the cryo-trapping and subsequent thermal release from the trap but there is fractionation due to re-absorption onto the freshly crushed rock matrix (quartz or calcite) powder.Compound specific carbon isotope analysis of hydrocarbon gases (C1-C5 except M-C4) and CO2 released from a FI sample from the Cooper-Eromanga Basin was achieved for the first time as a proof of concept of the technique. Preliminary research on FI gases has been carried out in the Browse Basin, Australia.